Course review horay and critical thinking skills: the effective teaching model for students’ grammar competence in remote EFL classrooms - Mukminatus Zuhriyah; Maskhurin Fajarina (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
Since the COVID-19 pandemic, EFL lecturers need to be creative in handling their remote teaching. However, scarce studies investigated the use of course review horay (CRH) and students’ critical thinking skills (CTS) in remote EFL classrooms especially in grammar classes. The study aimed to explore whether or not CRH was more effective than explanation model to teach grammar and the students having high CTS had better grammar competence than those of low CTS. This experimental study employed a 2x2 factorial design. The population was the second semester students of non-English departments in a private university in East Java, Indonesia. The sample was four groups comprising of two groups (high and low CTS) in the experimental class and two groups (high and low CTS) in the control class. To categorize them into high and low CTS, an Indonesian argumentative essay writing test was used. After six meetings of treatment, the students did the grammar test. The grammar scores were, then, analyzed using ANOVA and TUKEY tests. The results indicated that CRH was more effective and the students with high CTS possessed better grammar competence. The present study implies that CRH and CTS created a joyful learning atmosphere in remote grammar teaching.